Cameroon : Second Reviews Under The Extended Credit Facility And The Extended Fund Facility Arrangements, And Requests For Waivers For Performance Criteria Applicability And Modification Of Performance Criterion-Press Release; Staff Report; And Statement By The Executive Director For Cameroon. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
Following two years of COVID-19 challenges, Cameroon, the largest economy in the Central African Economic and Monetary Union (CEMAC), is facing a new policy environment. The nascent economic recovery from mid-2021, supported by higher oil prices and non-oil production, is now subject to greater uncertainties with spillovers from the war in Ukraine, high inflationary pressures, especially on food and fuel prices, and a tightening of global financial conditions. Low vaccination rates also leave the country vulnerable to further COVID-19 waves. In July 2021, the IMF's Executive Board approved three-year arrangements under the Extended Credit Facility (ECF) and the Extended Fund Facility (EFF) for SDR 483 million (about USD 689.5 million, or 175 percent of Cameroon's quota) to support the country's economic and financial reform program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Cameroon